2022
DOI: 10.1039/d2se00859a
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Organosolv and Kraft lignins into value-added compounds assisted by an acidic deep eutectic solvent

Abstract: In this study, an acidic deep eutectic solvent (DES) was used as benign solvent to valorise technical lignins by breaking down their structure into value-added aromatic compounds. The action of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 71 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…18b) to get the final product. The catalytic conversion of kraft lignin and organosolv was also carried out by Sosa et al 163 using acidic DESs made of ChCl : OA at 80 °C. Further addition of H 2 SO 4 and H 2 O 2 as a co-catalyst to the DESs system improves the lignin depolymerization from kraft and organosolv lignin by up to 26.1% and 27.8%, respectively.…”
Section: Usedmentioning
confidence: 99%
“…18b) to get the final product. The catalytic conversion of kraft lignin and organosolv was also carried out by Sosa et al 163 using acidic DESs made of ChCl : OA at 80 °C. Further addition of H 2 SO 4 and H 2 O 2 as a co-catalyst to the DESs system improves the lignin depolymerization from kraft and organosolv lignin by up to 26.1% and 27.8%, respectively.…”
Section: Usedmentioning
confidence: 99%
“…Besides, in previous reports, acidic DESs had been applied in lignin conversion. For example, Lopes et al reported that dissolution of lignin in acidic DES favored the formation of lignin oligomers, which could be further convert into syringol, acetosyringone, vanillic and syringic acids 48 . Yuan et al described that phenolic diketones could be obtained from lignin oil after acidic DES dissolution 49 .…”
Section: Characterization Of the Regenerated Lignin From The Des Solu...mentioning
confidence: 99%
“…Lignin properties, mainly ionizable functional groups and molecular weights, were studied for their effects on the LNP formation. Three types of lignin (i.e., kraft lignin (KL), organosolv lignin (OL), and ethanol soluble lignin (EKL)), which are commonly reported as starting materials for value-added lignin application, 44 were studied covering a reasonable range of ionizable functional group contents and molecular weight distributions. As summarized in Table 1, KL had 14% and 41% higher phenolic groups than OL and EKL, respectively.…”
Section: Effects Of Lignin Properties On the Lnp Formationmentioning
confidence: 99%